2018
DOI: 10.1148/rg.2018170175
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Coronary Artery Aneurysms:From the Radiologic Pathology Archives

Abstract: Advances in medical diagnosis reveal that coronary artery aneurysms (CAAs) may develop in several clinical scenarios and manifest variable symptoms, imaging appearances, and outcomes. Aneurysms are pathologically classified into three groups: atherosclerotic, inflammatory, and noninflammatory. The last category is associated with congenital, inherited, and connective tissue disorders. Overlap exists among the groups, because secondary atherosclerotic change may be present in an aneurysm of any cause. Atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 170 publications
(207 reference statements)
1
33
0
5
Order By: Relevance
“…CAA constitutes localized dilation of a coronary artery segment by more than 1.5-fold, tions; with these causes, most CAAs occur along major coronary arteries in the epicardial space (1)(2)(3)(4). IMCA as exhibited in our patient is very rare with an unknown incidence; extensive review of the literature revealed a case report that introduced IMCA arising from the septal branch of the left anterior descending artery (LAD), secondary to primary percutaneous transluminal coronary angioplasty (5).…”
Section: Discussionmentioning
confidence: 77%
“…CAA constitutes localized dilation of a coronary artery segment by more than 1.5-fold, tions; with these causes, most CAAs occur along major coronary arteries in the epicardial space (1)(2)(3)(4). IMCA as exhibited in our patient is very rare with an unknown incidence; extensive review of the literature revealed a case report that introduced IMCA arising from the septal branch of the left anterior descending artery (LAD), secondary to primary percutaneous transluminal coronary angioplasty (5).…”
Section: Discussionmentioning
confidence: 77%
“…Multimodality imaging provides excellent assessment of coronary artery aneurysms. 9,10 Transthoracic echocardiography is useful for detection of the aneurysm and assessment of left and right ventricular function and hemodynamic evaluation, but transesophageal echocardiography allows a more detailed anatomic assessment of the aneurysm. Multidetector cardiac computed tomography provides useful information about the size, extent, and relationship of the aneurysm to adjacent structures.…”
Section: Discussionmentioning
confidence: 99%
“…CAAs can undergo luminal thrombosis. [ 3 ] Over time, these findings can lead to myocardial ischemia with resultant ischemic cardiomyopathy, scarring, and remodeling.…”
Section: Discussionmentioning
confidence: 99%